Association of proton pump inhibitor use with endothelial function and metabolites of the nitric oxide pathway: A cross‐sectional study. Issue 2 (4th February 2021) - Nolde, Michael; Bahls, Martin; Friedrich, Nele; Dörr, Marcus; Dreischulte, Tobias; Felix, Stephan B.; Rückert‐Eheberg, Ina‐Maria; Ahn, Nayeon; Amann, Ute; Schwedhelm, Edzard; Völzke, Henry; Lerch, Markus M.; et al.
Abstract: Study Objective: Long‐term intake of proton pump inhibitors (PPIs) might increase the risk of cardiovascular events. One suggested mechanism is that PPIs inhibit the enzyme dimethylarginine dimethylaminohydrolase (DDAH) and thereby block the degradation of endothelial asymmetrical dimethylarginine (ADMA). Excess ADMA in turn leads to impaired endothelial nitric oxide (NO) generation. So far, this mechanism has only been established in human cell cultures. Previous studies that examined this pathway in human populations measured circulating ADMA and found no association with PPI use and excess plasma ADMA. But in a recent study, plasma ADMA was not correlated with intracellular ADMA. We therefore focused on changes in plasma citrulline as an indicator for potential DDAH inhibition. Design: We analyzed the association between regular daily PPI intake and flow‐mediated dilation (FMD) of the brachial artery as well as plasma concentrations of citrulline, arginine, ADMA, and symmetric dimethylarginine using inverse probability weighting to adjust for confounding and censoring. Data Source: Data of 1298 participants from two independent cohorts of the population‐based Study of Health in Pomerania were used. Patients: Participants of the population‐based Study of Health in Pomerania are a stratified random sample of the study region. Intervention: Regular daily intake of PPIs. Measurements: FMD of the brachial artery and plasma concentrations of citrulline, arginine, ADMA, and symmetric dimethylarginine. Main Results: Eighty‐seven participants (57.5% female) were regular daily users of PPIs. In the fully adjusted models, associations were identified for FMD and plasma citrulline concentrations. PPI users revealed a 0.99% (95% CI: −1.96 to −0.02) lower FMD and 3.03 µmol/L (95% CI: −4.96 to −1.10) lower plasma citrulline levels as compared to non‐users. Conclusion: Our data provide evidence that long‐term intake of PPIs might inhibit human DDAH activity, resulting in impaired endothelial NO production and reduced vascular function. In the long run, this might explain an increased risk for cardiovascular diseases associated with long‐term PPI use.